HGG-16. DISSECTING THE EFFECT OF ATM DELETION ON RADIOSENSITIVITY IN DIFFUSE MIDLINE GLIOMAS WITH H3K27M MUTATION. (1st June 2021) - Guerra Garcia, Maria; Deland, Katherine; Luo, Lixia; Ma, Yan; Williams, Nerissa; Stewart, Connor; Kirsch, David; Reitman, Zachary
Abstract: Diffuse midline gliomas (DMGs) are responsible for a large proportion of childhood brain tumor deaths. Currently, radiation therapy is thought to be one of the most effective treatment options, but more than 90% of children still die within 2 years of diagnosis. DMGs are defined by somatic histone 3 K27M (H3K27M) mutations that have been shown to promote the G0/G1 to S cell cycle transition. The majority of DMGs also contain loss-of-function mutations in TP53 . Prior research demonstrated that orthotopic xenograft and primary mouse models of non-H3K27M-mutated gliomas with inactivation of p53 are preferentially radiosensitized by inactivation of Ataxia Telangiectasia Mutated (ATM), a kinase that mediates DNA repair in response to DNA damage caused by radiation. The high frequency of mutations that deregulate p53 in DMGs raises the possibility that H3K27M-mutant DMGs may also be radiosensitized by ATM inhibition, representing a unique therapeutic opportunity. Here, we hypothesize that H3K27M-mutant DMGs that have loss of function of p53 will be radiosensitized by loss of ATM. To test this hypothesis, we used the RCAS-TVA viral gene delivery system to generate genetically-faithful primary mouse models of H3K27M-mutant DMG with p53 deletion, and we used Cre recombinase to delete Atm in the tumor cells of these mice and generated littermate controls that retained Atm . Mice were imaged weekly via luciferase-based bioluminescence to track tumor development and irradiated with three daily fractions of 10 Gy after tumor detection. We subsequently quantified the survival of mice without neurological decline following irradiation. In separate cohorts, we collected primary tumors after irradiation to verify H3K27M expression and to assess cell cycle arrest and mechanisms of cell death. These studies will elucidate mechanisms by which ATM inactivation can radiosensitize H3K27M-mutant DMGs with nonfunctioning p53, which will guide the design of clinical trials testing ATM inhibitors in DMG patients.